Determinación de la hiperbilirrubinemia y su incidencia con el desarrollo de ictericia en neonatos del hospital general Martín Icaza, Provincia Los Ríos, septiembre 2017 a febrero 2018 - Sánchez García, Edison Rafael (2018)
The present research project is based on pragmatism because it has a relation of theory that is based on the foundation of theory and practice, in the Clinical Laboratory exams thus allowing to have a practical theoretical relationship. Jaundice, a common disorder in newborns, refers to the yellowing of the skin and the sclera (the white of the eye) caused by an excess of bilirubin in the blood. The objective of the research was to establish the importance of the early determination of bilirubin in blood and its relationship with the diagnosis of hyperbilirubinemia and jaundice in neonates of the general hospital Martin Icaza, Los Ríos Province, September 2017 to February 2018. Methodology, quantitative, inductive-deductive, analytical and laboratory approach. The sample consisted of 50 infants. The results obtained show that of the total number of neonates treated, 98% had high bilirubin levels, while 2% had normal levels. Likewise 60%, had 35 weeks of gestation, 24% with 36 weeks and 16% 37 weeks of gestation. The blood type of 32 mothers was of group O + that corresponds to 64%, while the group O- of 18 mothers with 36%, which totals 100% of the study sample, which is 50 cases. In conclusion, the main risk factors are: HR factor and gestation time.